2022
DOI: 10.1136/bmjopen-2021-057888
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job satisfaction, burnout syndrome and depressive symptoms in physicians: a cross-sectional study based on the employment demand–control model using structural equation modelling

Abstract: ObjectiveTo evaluate the relationship between job satisfaction, burnout syndrome (BS) and depressive symptoms (DS) based on the job demand–control framework model on a nationally representative sample of physicians working in the Peruvian Health System.SettingWe carried out a secondary data analysis of the National Survey of Satisfaction of Users in Health 2016 in Peru.Primary and secondary outcome measuresOur study assessed the development of the predictive model and had two parts: (1) to evaluate the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…In this regard, in previous studies conducted in Peru and Mexico, family separation, number of children and relationship with a partner were associated with burnout [ 45 , 61 ]. The results of this study confirm the psychosocial model, which maintains that the origin and development of BS occurs mainly in the workplace [ [62] , [63] , [64] ], and theories of social and organizational exchange [ 26 , 65 ].…”
Section: Discussionsupporting
confidence: 81%
“…In this regard, in previous studies conducted in Peru and Mexico, family separation, number of children and relationship with a partner were associated with burnout [ 45 , 61 ]. The results of this study confirm the psychosocial model, which maintains that the origin and development of BS occurs mainly in the workplace [ [62] , [63] , [64] ], and theories of social and organizational exchange [ 26 , 65 ].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, job satisfaction affects burnout, and burnout influences depression. 26 Research results on sex differences in burnout are not consistent, but some studies that targeted specific occupations found that women are slightly more vulnerable to burnout than men. 27 28 Therefore, when job satisfaction is low, women may be more prone to experiencing burnout, and this could increase the risk of depression.…”
Section: Discussionmentioning
confidence: 98%
“…Linking job stress to depression, Wang and Patten hypothesized that employees who reported high psychological demands, low decision latitude, high levels of physical exertion, job insecurity, or lack of support from co-workers would be more likely to suffer from major depression than individuals who reported low stress in those areas [32]. Combing through the studies on the relationship between job satisfaction and depression, we found that most of the studies were based on a specific occupation (doctors [27] or nurses [33]), limited sample areas (data were usually collected in a specific workplace [34]), or limited sample size (less than 10,000 respondents [29]), so the conclusions acquired were targeted and difficult to generalize. As the main workers in current society, adults aged 35-60 years usually carry the responsibility and burden of working, so the association between their job satisfaction and depressive symptoms is still worth further exploration.…”
Section: Introductionmentioning
confidence: 86%
“…Some meta-analyses have found that job satisfaction had a significant negative effect on depression [73,74], which suggests that higher job satisfaction results in less depression. Although job satisfaction is a concept based on the worker's perception, it directly reflects the actual conditions of the workplace [27]. Poor working conditions are often associated with low income and low job security, the absence of pensions and health benefits, greater risk of layoff, and lack of social protection from unions and labor laws for employees [75][76][77][78].…”
Section: The Direct Effect Of Job Satisfaction On Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation